Ultra-high temperature flexure and strain driven amorphization in polycrystalline boron carbide bulks. (15th March 2022) - Demirskyi, D.; Sepehri-Amin, H.; Suzuki, T.S.; Yoshimi, K.; Vasylkiv, O.
Abstract : The temperature dependence of the flexural strength of sintered boron carbide was studied. At temperatures above 2000 °C, B4 C showed an ultrahigh flexural strength exceeding 1 GPa which was accompanied by a change in the deformation mechanism from brittle fracture to plastic deformation. Scanning transmission electron microscopy (STEM) observations revealed that the amorphization can be of microstructural origin for the observed plasticity in B4 C at temperatures above 2000 °C and a strain rate of 310 −3 s −1 . The amorphization occurs inside of the severely deformed grains. Flexural tests below 2000 °C provided evidence for the formation of stacking faults or dislocations, which are ordinary defects after the flexural tests. The results at 2000 °C suggest that the magnitude of the tensile stresses imposed on the B4 C grains during deformation in flexure and the total strain transferred to a ceramic during the deformation process play the dominant role in the crystalline-amorphous transformation. Graphical abstract: Image, graphical abstract